(untitled) (Journal of Asian Development Studies, 2025)
Despite limited educational resources, public school teachers in Pakistan are increasingly utilizing affordable technologies to improve their instructional methods. This study aims to investigate the trends (here, trends refer to patterns or directions of change) in the use of different types of technologies in public schools, as well as the difficulties educators face when integrating technology into the classroom, and to provide immediate solutions to overcome these challenges. This study will be exploratory. The methodology used for this study is a qualitative approach. The present study will employ the phenomenological method. The findings show that trends in teaching underwent rapid changes after the COVID pandemic. -19, teachers primarily used kinesthetic learning methods, such as role-play, charts, and 3D models. Now, teachers are shifting to technology, but they are utilizing low-cost technologies, including mobile devices, tablets, microphones, social media, open-source software, and mobile applications. Mobile phones were used for assessment and assignments. These technological tools have been successfully integrated into classroom instruction. The integration of technologies in educational settings has significantly enhanced the process of personalized learning. It has provided students with improved access to educational resources, facilitated more opportunities for practice and feedback, and contributed to the development of essential skills. These trends suggest that, with appropriate government financial support, teacher training and incentives can improve educational outcomes in resource limited settings. This highlights the need for targeted investment in teacher training, workshops, and improvements to curriculum and infrastructure.